Perfis dos estudantes que trabalham durante a graduação: uma análise comparativa dos cursos de licenciaturas em Ciências - D'Agostino, Lídia Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In Brazil, students with low socioeconomic status tend to enroll in night graduation courses, especially degrees, due to the greater ease of access and as an option that allows to reconcile a working day with studies. However, the bibliography in the science education field still has few studies on the characteristics of these undergraduates in relation to their involvement with work. In this respect, this study intends to identify the profile of students in Licentiate Science courses that work. The microdata from the ENADE 2017 student questionnaire were used as the database for this empirical investigation. The data were managed using the R language, initially, only students attending chemistry, physics and biology courses were selected, totaling 10,196 subjects. Then, three different types of student were created based on the weekly hours of work and considering the sociological literature on this profile of students: Student (0h), Student-worker (up to 8 hours) and Worker-student (more than 9 hours). To build the profile based on student types, 21 questions from ENADE 2017 were selected, and organized into three dimensions: Socioeconomic, Academic and Professional. In order to investigate the associations of each answer with the type of student, the chi-square test and graphical schemes of their standardized residuals were used, which allows to differentiate visually the existing associations and anti-associations. As a result, it was observed in the Socioeconomic Dimension that the Student is associated with parents with a secondary level of education, the Student-worker has parents with higher education, while the Worker-Students are associated with parents with a low level of education. The Academic Dimension showed us that Students and Student-workers devote themselves to study about three times more than Worker-students. The Professional Dimension highlighted that the only type of student who really intends to practice teaching are Student-workers, that choose the course because they believe it is their calling. Joining the dimensions, it was possible to notice that the Student is similar to the Student-Worker, mainly due to the relationship with their parents education and forms of study, with the vocation for a degree a characteristic of the latter. The Student-Worker, on the other hand, distances himself in all aspects from the other two and is well-marked by his relationship with work and income.

No Brasil, estudantes com baixo nível socioeconômico tendem a ingressar em cursos de graduação noturnos, principalmente licenciaturas, em função da maior facilidade de acesso e por serem uma opção que permite conciliar uma jornada de trabalho com os estudos. Entretanto, a bibliografia da área de educação de ciências ainda tem poucos estudos sobre as características desses licenciandos em relação ao envolvimento com o trabalho. Nesse sentido, este estudo buscou identificar o perfil dos estudantes dos cursos de Licenciatura em Ciências que trabalham. Os microdados do questionário do estudante do ENADE 2017 foram utilizados como base de dados para esta investigação empírica. Os dados foram trabalhados utilizando a linguagem R, primeiramente foram selecionados apenas os estudantes de licenciaturas presenciais de Química, Física e Biologia, totalizando 10.196 sujeitos. Então, três diferentes tipos de estudante foram criados com base nas horas semanais de trabalho e considerando a literatura sociológica sobre esse perfil de estudantes: Estudante (0h), Estudante-trabalhador (até 20h) e Trabalhador-estudante (mais de 21h). Para construir o perfil com base nos tipos de estudante foram selecionadas 21 questões do ENADE de 2017, organizadas em três dimensões: Socioeconômica, Acadêmica e Profissional. Para investigar as associações de cada resposta com o tipo de estudante, foi empregado o teste do qui-quadrado e esquemas gráficos de seus resíduos padronizados, o que permite distinguir de maneira visual as associações e anti-associações existentes. Como resultado, foi observado na Dimensão Socioeconômica que o Estudante está associado a pais com nível de escolaridade médio, o Estudante-trabalhador possui pais com nível superior, enquanto os Trabalhadores-estudante estão associados a pais de baixa escolaridade. A Dimensão Acadêmica nos mostrou que os Estudantes e Estudantes-trabalhadores se dedicam aos estudos cerca de três vezes mais que os Trabalhadores-estudantes. A Dimensão Profissional ressaltou que o único tipo de estudante que pretende realmente exercer o magistério são os Estudantes-trabalhadores, escolhendo o curso por acreditar ser sua vocação. Unindo as dimensões foi possível notar que o Estudante é semelhante ao Estudante-Trabalhador, principalmente em função da relação com a formação dos pais e formas de estudo, sendo a vocação pela licenciatura característica do último. Já o Trabalhador-estudante se distancia em todos os aspectos dos outros dois e é amplamente marcado pela relação com o trabalho e a renda.
Profile of students who work during undergraduation: a comparative analysis of licenciate science courses
Keywords: ENADE; Licenciatura em Ciências; Estudantes que trabalham